Optimization of Binocular Microscope with Micro Digital Camera for Measuring Seminiferous Tubules Epithelium Height - Sutriyono, Sutriyono (Biology, Medicine, & Natural Product Chemistry, 2016)
Binocular microscope optimization using micro digital camera to measure seminiferous tubules epithelium of mouse testis (Mus muculus) was completed. This research was conducted at Biology Laboratory of Faculty of Science and Technology UIN Sunan Kalijaga. The purpose of this study was to determine the height of the seminiferous tubules epithelium of mouse testis using micro digital camera. A computer was connected with binocular microscope and optilab advance, then calibration of optilab advance were done on objective lens magnification at 4x, 10x and 40x with 10x ocular lens. The analysis used was descriptive analysis. The mean of the seminiferous tubules epithelium height is 105.6 μm. Optimization on computer and binocular microscope with micro digital camera can be used to measure seminiferous tubules epithelium.